"Assessment knowledge is important, but …": How contextual and experiential factors mediate assessment practice and training needs of language teachers. (June 2018) - Yan, Xun; Zhang, Cong; Fan, Jason Jinsong
Abstract: This qualitative study examined how contextual and experiential factors mediate language assessment literacy (LAL) development for three secondary-level English as a foreign language (EFL) teachers in China. Through semi-structured retrospective interviews, we found that teachers (1) demonstrated a distinct LAL profile and (2) indicated stronger training needs in assessment practice than in assessment theory. These two findings can be explained by a combination of teachers' assessment experience, stakeholder network, assessment policies, assessment training resources, and practical constraints. Findings of this study contribute to our current understanding of LAL development and assessment training for language teachers.